Benzoylmethyl 4-chlorobenzoate - Jin, Yi (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(15)H(11)ClO(3), contains three molecules, A, B, and C. Molecules A and B are aligned edge-to-face, whereas molecules B and C are aligned almost parallel to each other. The crystal structure displays C—H⋯π and π–π [centroid–centroid distances of 3.960 (4), 3.971 (4) and 3.971 (4) for molecules A, B and C, respectively] parallel-displaced interactions, and C—H⋯O hydrogen bonds.